Chronic endometritis and recurrent reproductive failure: a systematic review and meta-analysis - Ticconi, Carlo; Inversetti, Annalisa; Marraffa, Serena; Campagnolo, Luisa; Arthur, Jephtah; Zambella, Enrica; Di Simone, Nicoletta (Frontiers in Immunology, 2024)
Background The endometrium holds a crucial role in reproduction by supporting blastocyst adhesion, cytotrophoblast invasion and fetal development. Among the various uterine disorders, endometritis, particularly chronic endometritis (CE), has gained attention due to its association with adverse reproductive outcomes (recurrent pregnancy loss (RPL), recurrent implantation failure (RIF), and infertility). The association between CE and adverse reproductive outcomes stresses the necessity for comprehensive diagnostic and therapeutic strategies to optimize fertility outcomes and support individuals in their journey towards parenthood. Aim To explore the relationship between CE and reproductive disorders. Methods Following PRISMA guidelines, a systematic review and meta-analysis using published data from 1990 to 2024 were carried out. Results A population of 1,038 women was included. Regarding CE-infertility association, a positive correlation was found, with 19.46% CE rate in infertile women compared to 7.7% in controls (OR: 2.96, 95% CI 1.53-5.72, p 0.001). No significant association was observed between RIF and CE (OR: 1.10, 95% CI 0.26-4.61, p 0.90), CE rates in both groups were relatively comparable, with 6.35% in women with RIF and 5.8% in controls. On the opposite, a strong association between CE and RPL was found, reporting a CE rate of 37.6% in RPL cases compared to 16.4% in controls (OR: 3.59, 95% CI 2.46-5.24, p < 0.00001). Conclusions CE appears to be associated to infertility and RPL, while no significant association was noted in cases of RIF. Systematic review registration https://www.crd.york.ac.uk/prospero/#recordDetails PROSPERO, identifier CRD42024541879.